The Eurozone under serious pressure: Regional economic cycles in the Monetary Union need to be stabilised - Sebastian Dullien; Daniela Schwarzer (Stiftung Wissenschaft und Politik (SWP), 2005)
In debates about the future of the EU, the eurozone is regularly held up as a stable core element that could potentially deepen cooperation across broad policy areas. Undoubtedly the 12 EMU Member States have a keen interest in maintaining and consolidating the European Monetary Union as a framework for stability and growth. This makes it all the more alarming that regional economic cycles are putting serious pressure on the eurozone, generating major potential for political conflict. In June the Council of Ministers will ponder on the European Union's response to this problem. A European transfer mechanism to stabilise regional economic cycles could avert the danger of the Monetary Union breaking up. A European corporate tax scheme or a form of European unemployment insurance system, each of which would complement their respective national counterparts, would have the desired effect without increasing contributions. This would give Europe the kind of social component it is currently missing - a fact criticised in the debate about the European Constitution. (SWP-Comments / SWP)
Keywords: 320